Konseling Karir Dengan Kegiatan My Collage Untuk Mendeskripsikan Career Time Perspective Mahasiswa - Afriyati, Vira; Ahman, Ahman; Saripah, Ipah (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2023)
Perspective of time as one of the important determinants of behavior in one's life. Likewise, the career time perspective or career time perspective. The importance of understanding how a person views or how his perspective on time will affect how mature his career is. This article aims to describe the Career Time Perspective (CTP) of Guidance and Counseling students at the University of Bengkulu. This research is qualitative research with 8 students as research subjects. The treatment used is my collage activity. This research was analyzed using descriptive analysis. The results of the study show that the career time perspective of each student in each time zone influences each other. The past, present and future zones are related. The results of this study can be used as a basis for developing student career development programs.